Gravhøj med flintdolke og børnegrave: Overgangen fra enkeltgravskultur til senneolitikum i Vesthimmerland - Henning Nielsen, Bjarne (Kuml, 2025)
A barrow containing flint daggers and child graves The transition from the Single Grave culture to the Late Neolithic in Vesthimmerland Almost 40 years ago, a farmer and his son were removing stones from a newly ploughed field (fig. 1, VMÅ 2251), unaware that the stones constituted graves in a low burial mound. On completing the job and reviewing their work, they were surprised to find two very large flint daggers on the surface of the levelled soil. They took the daggers home with them and only rarely showed them to guests and family members. But rumours of their existence spread and eventually reached both the National Museum of Denmark and the local Vesthimmerlands Museum. Since then, repeated attempts have been made to have the flint daggers handed over to the museums for evaluation: Were they treasure trove (danefæ) or not? A few years ago, the author had the opportunity to see and measure the daggers and have them photographed (figs. 2-3). The final decision regarding their treasure trove status is still awaited. The flint daggers are early types, dating from the beginning of the Danish Late Neolithic. There are some other contemporaneous localities in the near vicinity: Two flint-knapping workshops (fig. 1, VMÅ 2439 and note 4) with numerous fragments of daggers and sickles, postholes associated with two houses (fig. 1, VMÅ 867) and a further burial mound (fig. 1, FHM 1615 Kirkebjerget), exclusively containing child graves, but sealed by what appears to be an adult grave. When removing the topsoil over the burial mound where the two flint daggers were found (fig. 1, VMÅ 2251), it was discovered that this mound covered several child graves, as well as at least one grave of an adult woman (fig. 4, A2, fig. 6a+b). The graves were arranged in a circle around a central grave containing the well-preserved remains of a child only 6-9 months of age (fig. 4, A13). This grave had maximum dimensions of 1.32 m x 0.85 m and a depth of 0.6 m. Another well-preserved grave was excavated to the west of the central grave. It contained the remains of 1½-year-old child buried in a wooden coffin, 1.1 m in length and 0.25 m in width (fig. 4, A10, figs. 8-9). A grave to the southwest could be that of an adult because a small beaker was found there (fig. 7). Most of the other stone-set graves contained neither skeletal material nor grave goods. These can probably be termed Oder cists, which are usually thought to have been constructed for children and are rather common in northern Jutland (fig. 4, A3, A4, A5, A6 and possibly A7). The child in the central grave was approximately 6 months old, judging from the development of the teeth and a general evaluation of the skeleton (figs. 10-12). A limb bone was 14C dated to 3772 60± BP (note 6). This date seems a little too late, since a beaker was found in grave A3 and the central grave should be the earliest, and the latest grave(s) should have the flint dagger(s). Strontium analysis was undertaken on the teeth of the presumed woman in grave A2. The Sr86/87 ratio was 0.71003, showing that the individual was most likely local, according to the local baseline. The most important finds from this locality are therefore the two very large flint daggers and the skeletal material, especially that of children, recovered during the 2001 excavation. The infant in the central grave is clearly important due to its significant position and the preservation of its remains. Child graves were also found in a central position in the barrows at Kirkebjerget and Strandet Hovedgård, but only the teeth were preserved at these two sites. In both cases, the child graves were also positioned tangentially to the central grave and were sealed by graves that were most certainly of adults (containing flint daggers or flint axes). The small cists appear to belong to children and this grave type is also found as secondary graves in barrows, with an adult in the central grave, or even in settlements. It seems that for a short while the inhabitants of this region, Himmerland, Salling and Mors, invested great efforts in burying their children when they died, also those of an age not usually considered to be ‘a real human being’, i.e. under 4 years of age. It should be noted, however, that the beakers in these graves are small and that flint daggers and flint axes are associated with the adult graves in the barrows. The children were probably not counted as real people anyway. Nevertheless, it is striking that the primary graves in these three barrows were constructed for very young children. This must mean that these children were predestined for a certain position in the social hierarchy, perhaps regardless of their gender. One may wonder why these barrows were sealed with tools or weapons characteristic of adult men; in the case of Malle Østergaard with some of Denmark’s finest flint daggers. This may reflect the demise of an individual family, but here at the transition from the Single Grave Culture to the Late Neolithic, it may also mirror a development in the family-, kinship- and social structure indicating an even more pronounced hierarchy. It is worth noting that only a short distance separates the barrows containing multiple child graves, such as those at Kirkebjerget and Malle Østergaard. These two barrows exemplify the relative proportions of child and adult deaths in two neighbouring families. Was this level of child mortality common and was this relative distribution normal? Either way, the Malle Østegaard site constitutes an excellent supplement to our current knowledge about child graves at the end of the Single Grave Culture and the transition to the Late Neolithic.